Jubilees and Hellenistic Encyclopaedism - Hartog, Pieter B. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2019)
The final form of the book of Jubilees is commonly dated to the Hellenistic period. It may come as no surprise, therefore, that various parallels between Jubilees and Greek scholarship have been discovered. Yet scholars remain divided on Jubilees' attitude towards Greek culture. In this article, I argue that Jubilees is fully conversant with global intellectual developments in the Hellenistic period and exhibits a type of encyclopaedic rhetoric similar to non-Jewish scholarly writings from this period. At the same time, Jubilees exhibits a local outlook, as it emphasises the timelessness and distinctiveness of the Jewish nation and its laws. Hence, the book must be understood as a "glocal" work, in which global and local trends merge and are intricately intertwined.